Peningkatan Pemahaman Realitas Dan Dampak Sosial Pernikahan Dini Di Ypmi Miftahul Huda Ulujami Jakarta Selatan - M. Aska Askia; Duna Izfanna; Rifaldi Nurul Akbar (Jurnal Pengabdian Masyarakat (Bisma), 2024)
The Islamic religion implies marriage as the only form of living in pairs that is justified and recommended to be developed in forming a family. According to Law Number 1 of 1974, marriage is an inner and outer bond between a man and a woman as husband and wife to form a happy and eternal family (household) based on the belief in the Almighty God. This activity uses a true experimental pre-test approach. -post-test design using lecture, discussion, and question and answer methods to determine the level of knowledge and understanding of the participants both before the activity starts and after the activity is completed. The increase in knowledge and understanding from pre-test to post-test is meaningful for participants and is a benchmark for the success of this activity. Participants gain additional knowledge and understanding regarding the prevention of early marriage, and it is hoped that participants will share their knowledge, especially in the surrounding environment where participants live. Before the activity was carried out, 80% of workshop participants did not understand the material related to early marriage. However, there is an increase in knowledge and understanding. From the results of the posttest, as many as 98% of participants understood and gained better knowledge about early marriage. The results of the post-test showed that participants in counseling activities gained increased knowledge and insight regarding what drives early marriage, the risks that can occur, and the impact they will get. Workshop participants also know and understand what must be done to prevent early marriage.